The global burden of aortic aneurysm attributable to hypertension from 1990 to 2021: Current trends and projections for 2050 - Guanghui Yu; Pei Chen; Changhao Sun; Peng Liu (PLoS ONE, 2025)
Background and Objectives Hypertension is a major risk factor for aortic aneurysm (AA), but the global, regional, and national patterns of its related disease burden are not well studied. This study uses 2021 GBD data to examine trends in hypertension-related AA from 1990 to 2021, project future trends, and provide evidence for targeted prevention strategies. Methods This study extracted data on mortality, disability-adjusted life years (DALYs), age-standardized mortality rate (ASMR), and age-standardized DALY rate (ASDR) associated with AA attributable to hypertension from the 2021 GBD study. The estimated annual percentage change (EAPC) was employed to assess burden trends from 1990 to 2021.The study utilized the Bayesian Age-Period-Cohort (BAPC) model to project disease trends from 2022 to 2050. Additionally, decomposition analysis and frontier analysis were employed to conduct a more comprehensive examination of the data. Results In 2021, 26,782 deaths and 529,977 DALYs were caused by hypertension-related AA globally, reflecting increases of about 49% and 47% since 1990. However, both ASMR and ASDR declined worldwide. From 1990 to 2021, the ASDR for hypertension-related AA decreased by 54.08% and 15.56% in high-SDI and upper-middle-SDI regions, respectively, while it increased by 25.23%, 62.02%, and 17.99% in middle-SDI, lower-middle-SDI, and low-SDI regions. The disease burden is significantly higher in males than in females and increases with age.The findings from the decomposition analysis reveal that population growth and the aging process are the primary contributors to the escalating burden, with varying impacts across different regions. The frontier analysis identified 15 countries with the greatest potential for improvement. According to the BAPC model, the ASDR for females is projected to rise across the 20–80 age group, while for males, the increase is particularly pronounced in the 55–75 age group. Globally, the ASDR is expected to initially decline before gradually rising, reaching 12.07 per 100,000 by 2050, a 5% increase compared to 2021. Conclusion While the global number of deaths and DALYs attributable to hypertension-related AA continues to rise, the ASMR and ASDR are showing a declining trend. However, in middle, lower-middle, and low SDI regions, ASMR and ASDR remain on an upward trajectory. Projections indicate that the global ASDR will initially decline before gradually increasing, with an expected rise by 2050.